2022
DOI: 10.3390/cancers14225584
|View full text |Cite
|
Sign up to set email alerts
|

Histone Chaperones and Digestive Cancer: A Review of the Literature

Abstract: Background: The global burden of digestive cancer is expected to increase. Therefore, crucial for the prognosis of patients with these tumors is to identify early diagnostic markers or novel therapeutic targets. There is accumulating evidence connecting histone chaperones to the pathogenesis of digestive cancer. Histone chaperones are now broadly defined as a class of proteins that bind histones and regulate nucleosome assembly. Recent studies have demonstrated that multiple histone chaperones are aberrantly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 163 publications
0
0
0
Order By: Relevance
“…Defining the FACT complex as a novel target for cancer treatment enabled researchers to investigate Curaxin as a therapeutic treatment for HCC patients [ 32 ]. Curaxin, a small molecular inhibitor of FACT that induces chromatin trapping of FACT and significantly inhibits normal human FACT activities, causes intracellular acidification and apoptosis of cancer cells [ 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining the FACT complex as a novel target for cancer treatment enabled researchers to investigate Curaxin as a therapeutic treatment for HCC patients [ 32 ]. Curaxin, a small molecular inhibitor of FACT that induces chromatin trapping of FACT and significantly inhibits normal human FACT activities, causes intracellular acidification and apoptosis of cancer cells [ 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…(A) Potential implication of ASF1A in GM-CSFdependent inflammatory pathway.ASF1A inhibits the over-expression of GM-CSF. ASF1A depletion (dashed box) blocks (red cross) the inhibition pathway, which leads to the over-expression of GM-CSF, establishing an anti-tumor immunogenic response[32]. (B) The potential implication of ASF1A in Wnt signaling pathway is to cause the over-expression of β-catenin, which stimulates oncogene transcription[40].…”
mentioning
confidence: 99%
“…Histone chaperones are tightly linked to histone function, as their role in deposition and histone level control ensures an appropriate balance of incorporation and exchange (Hammond et al, 2017), which can be compromised during carcinogenesis. Like histone genes, histone chaperone genes are also dysregulated in cancer, including the H3-H4-cargoing chaperones ASF1, HIRA, CAF-1, DAXX, and DEK, the H3-H4 and H2A-H2B chaperone FACT, and the CENP-A-H4 chaperone HJURP (Ray- Gallet and Almouzni, 2022;Zhao et al, 2022). In terms of contribution to aneuploidy, several studies have shown the importance of histone chaperones in maintaining chromosomal stability, including increased levels of aneuploidy upon loss of FACT (Prendergast et al, 2020), ASF1 (Horard et al, 2018) and HJURP (Filipescu et al, 2017), mitotic defects and micronuclei following overexpression of DEK (Matrka et al, 2015), and expansion of ribosomal DNA (rDNA) repeats in absence of ASF1 (Houseley and Tollervey, 2011), which can be a source of chromosomal aberrations if inappropriately resolved (Daniloski et al, 2019).…”
Section: Histone Excess Compromises the Balance Of Histone Availabili...mentioning
confidence: 99%
“…Histone chaperones are required for histone storage, transport, post-translational modifications, nucleosome assembly, and histone turnover. The third review in this Special Issue describes the role of selected histone chaperones in the progression of digestive cancers and their prognostic significance [9].…”
mentioning
confidence: 99%